2018
DOI: 10.1159/000493156
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bubble CPAP Devices Using RAM Cannula for Extubation Failure in Very Low Birth Weight Infants: Randomized and Cohort Studies

Abstract: Introduction: Bubble continuous positive airway pressure (bCPAP) generates a variable pressure due to bubble size and frequency, and these pressure oscillations may contribute to lung recruitment and gas exchange. Single-outlet bCPAP devices generate larger pressure fluctuation than bCPAP devices with diffusers, but clinical efficacy is unclear. Our hypothesis was that a single-outlet bCPAP device (B&B Bubbler©) would decrease extubation failure and improve oxygenation compared with a bCPAP device w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
4
20
0
Order By: Relevance
“…Previous work by this group and others have shown that bCPAP provided via the RAM cannula dampens the potentially beneficial pressure fluctuations of bCPAP and decreases the pressure measured at the cannula prongs by $35% from the set pressure. 7,14,16,17 Similar decreases in pressure transmission have also been seen with the use of the RAM cannula for noninvasive mechanical ventilation. 18,19 If the RAM cannula is employed in the DR for CPAP and in the early management of respiratory distress syndrome (RDS), increased set pressures may be required to provide adequate intra-alveolar pressures to maintain adequate FRC and avoid early endotracheal intubation.…”
supporting
confidence: 53%
See 4 more Smart Citations
“…Previous work by this group and others have shown that bCPAP provided via the RAM cannula dampens the potentially beneficial pressure fluctuations of bCPAP and decreases the pressure measured at the cannula prongs by $35% from the set pressure. 7,14,16,17 Similar decreases in pressure transmission have also been seen with the use of the RAM cannula for noninvasive mechanical ventilation. 18,19 If the RAM cannula is employed in the DR for CPAP and in the early management of respiratory distress syndrome (RDS), increased set pressures may be required to provide adequate intra-alveolar pressures to maintain adequate FRC and avoid early endotracheal intubation.…”
supporting
confidence: 53%
“…Since the pressure fluctuations of bCPAP may play a role in gas exchange, the attenuation of these fluctuations by the RAM cannula could also affect our success. 4,5,7 During the 6-year period, we used either the FDA-approved bCPAP bottles from Babi.Plus or from B&B Bubbler, and these bottles may generate less pressure variations than the homemade version used at New York-Presbyterian or other available systems. 3 The infants in the DR did not have devices to close mouth, thus the CPAP levels could have been variable based on leak at mouth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations